Abundance and Diversity of Sea Cucumber (Holothuroidea) in Hajoran Beach, Central Tapanuli, North Sumatra - Bethanya, Ela Nanda; Zulkifli, Zulkifli; Samiaji, Joko (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Hajoran is a beach located on the coast of Pandan District, Tapanuli Tengah Regency, North Sumatra. This beach is one of the popular tourist destinations. It boasts high marine biodiversity, including a diverse array of marine organisms, which are part of the invertebrate animal group. This study was conducted in December 2024 along the Hajoran coast. The objective of this study was to determine the species, abundance, and diversity of sea cucumbers. The study also utilized supporting data, including water quality parameters that characterize the habitat conditions of sea cucumber species, such as temperature, salinity, depth, dissolved oxygen (DO), and total suspended solids (TSS). The study employed a survey method with sample collection using the quadrant transect method at three stations. Based on the study's results, four species were identified at the study site: Holothuria atra, H. scabra, Stichopus ananas, and S. chlorosomatus. The average abundance at all stations ranged from 9.600 to 14.000 ind/ha; the highest abundance was recorded at station III. The relative abundance values for each sea cucumber species ranged from 8 to 100%. The lowest relative diversity value was shown by the species S. chloronotus, with a value of 8% at station III. Conversely, the species H. atra exhibited the highest relative diversity value. The diversity index (H') of sea cucumbers at the research site was classified as moderate. Overall, the relatively stable and standardized water quality conditions at Hajoran Beach support the abundance and diversity of sea cucumber species